OPTIMIZATION MODELING OF EFFECT OF ACTIVITY INTERACTING STRUCTURAL DIVISIONS - Shevchenko, V. L. (Problems of Informatization and Management, 2005)
The method of construction of models of effects of activity of organizational structures by means of logistic SL-functions is offered. Modified the existing algorithm for setting the parameters of SL-functions. The problem of optimal distribution of funds by items of expenditure within one unit and optimal distribution of funds between several units is solved by the method of coordinate descent. An approach to modeling the dynamics of the organization's effect on the element is proposed.